The rainwater retention mechanisms in extensive green roofs with ten different structural configurations - Jun Wang (IWA Publishing, 2021)
Rainfall infiltration, rainwater retention, runoff and evapotranspiration (ET) are important components of the water balance in green roofs. These components are expected to be influenced by variations in the structural configurations (i.e., substrate layers) of green roofs. This study explores the influence of layered soil and green roof configurations on the rainwater retention capacity (RRC) of the roofs as compared to conventional improvements (i.e., soil conditioning and enhanced substrate depth). Ten different extensive green roof modules were designed by varying the substrate materials, substrate depths, storage/drainage layers and vegetation layers. For all modules, the RRCs ranged from 34 to 59%. The RRCs of layered soil were 1–4% higher than that for single-layer soil. The RRC increased by 13% in the presence of a water storage module. It can be concluded that highest RRC corresponds to a combination of high-permeability soil in the upper layer along with a relatively large water holding capacity in the deep layer. Water storage layer and layered soil could significantly delay the water stress in vegetation. The importance of wick irrigation, vegetation types, back-to-back rain events and the ET rate on the RRC were also discussed. HIGHLIGHTS The capacity of rainwater management and substrate moisture replenishment of green roof with water storage layer was pointed out.; Layered soil could significantly improve the substrate rainwater retention capacity compared with those obtained in single-layer substrates.; The increase rate of rainwater retention declined with an increase in depth beyond a certain point.;